2013
DOI: 10.1162/asep_a_00206
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Entry and Profitability of Domestic Firms: Evidence from China

Abstract: Profitability provides a yardstick for judging the operational efficiency, growth, and survival of a business enterprise. This study investigates the determinants of firm profitability in the Chinese manufacturing sector, with a focus on the impact of foreign entry on the profitability of domestic firms. Our findings show an inverted-U relationship between foreign entry and the profitability of domestic firms. Furthermore, we also find that the effect of foreign entry on domestic firm profitability varies acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…We find a strong and robust negative effect of FDI on PCMs of firms which suggests that FDI does increase the level of competition in Chinese manufacturing. This result stands in some contrast to studies on countries other than the PRC, which typically find mixed effects of FDI on competition (e.g., Co 2001, Chung 2001, Fu and Wu 2012.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We find a strong and robust negative effect of FDI on PCMs of firms which suggests that FDI does increase the level of competition in Chinese manufacturing. This result stands in some contrast to studies on countries other than the PRC, which typically find mixed effects of FDI on competition (e.g., Co 2001, Chung 2001, Fu and Wu 2012.…”
Section: Discussioncontrasting
confidence: 99%
“…Chung ( 2001) also finds mixed effects and suggests that the degree of competitive pressure imposed by FDI depends on both the entry mode and the various investment traits. The most interesting paper for our purposes is by Fu and Wu (2012) who study the effect of FDI on profits in Chinese firms. They find an inverted U-shape effect of FDI on profits, where profits tend to increase with smaller inflows of FDI but then decrease with larger flows.…”
Section: A Previous Studies On Fdi and Competitionmentioning
confidence: 99%
“…Speaking of the relationship of capital structure of domestic, foreign and joint ownership with profitability, one can refer to the data from an Indian study (Chhibber and Majumdar 1999), in which after controlling for a variety of firm and environment-specific factors, firms display relatively superior performance only when property rights belong to foreign owners at ownership levels providing unambiguous control at 51%. Also, the relationship between foreign entry and profitability of domestic firms has an inverted U-shape (Fu and Wu 2013). Furthermore, we also find that the effect of foreign entry on domestic firm profitability varies according to the ownership structure of domestic firms and the export intensity of foreign newcomers.…”
mentioning
confidence: 53%
“…At the same time, our contribution to the research of factors affecting profitability is the consistent patterns that we have identified in relation to groups of factors (production efficiency, internal financial factors, and external financial factors) in an unstable economy. In contrast to other studies of countries with unstable economies (Godart et al 2012;De Backer and Sleuwaegen 2003;Fu and Wu 2013), this paper contains a comprehensive study of the effect of the above-mentioned groups of factors in the context of industries and forms of ownership of enterprises. The obtained results are useful for effective industrial regulation in developing countries in unstable periods.…”
Section: Discussionmentioning
confidence: 99%
“…MNCs targeting their products at global markets are less likely to intensify local product market competition than are MNCs focused on serving the domestic market. Nevertheless, in previous work the market orientation of foreign entrants has not been shown to affect the performance of state-owned enterprises, even though this could affect the operational efficiency of private firms (Fu and Wu 2013).…”
Section: Foreign Direct Investment and Spillover Effectsmentioning
confidence: 87%